Increased B chromosome frequency and absence of drive in the fish Prochilodus lineatus - Oliveira, Claudio [UNESP]; Rodrigues Saboya, Silvia Maria [UNESP]; Foresti, Fausto [UNESP]; Senhorini, José Augusto [UNESP]; Bernardino, Geraldo [UNESP] (My University, 1997)
The neotropical freshwater fish species Prochilodus lineatus (Pisces, Prochilodontidae) shows 2n = 54 chromosomes plus supernumerary microchromosomes ranging in number from zero to seven among different animals. The transmission rates of B chromosomes were studied by the analysis of the parental and F1 generations in 10 controlled crosses performed with specimens from a natural population. The mean transmission rate observed for B chromosomes (k(B) = 0.511) was consistent with that expected from a regular meiotic behaviour orbs in both sexes and with the theoretical value under a Mendelian mode of transmission (0.5). Possible explanations for the dramatic increase in B frequency observed in this population during the last 10 years are discussed, bearing in mind the current absence of drive.
Keywords: B chromosome evolution; B chromosomes inheritance; Fish cytogenetics; Supernumerary chromosomes; Prochilodus lineatus